Community engagement in a livelihood restoration program: Linking geothermal land acquisition, empowerment, and livelihood sustainability - Dany Yuda Saputra; Herdis Herdiansyah; Indra Kertati (Interaction, Community Engagement, and Social Environment, 2026)
Background: This study examines how a Livelihood Restoration Program embedded in a community engagement framework contributes to livelihood recovery among households affected by land acquisition for a geothermal power plant in a mountainous district of West Sumatra, where energy transition, climate vulnerability, and resource‑dependent livelihoods intersect. Using the Sustainable Livelihoods Framework, the study explores changes in the livelihood assets and experiences of equity, empowerment, and engagement of citizens. Methods: A convergent mixed methods design was applied, combining a census survey of 52 project-affected households with in-depth interviews with 12 informants, including PAP beneficiaries and key stakeholders, followed by separate quantitative and qualitative analyses and integrated interpretation. Findings: Quantitative results showed a positive and statistically significant, but modest, effect of program participation on livelihood assets, explaining approximately 10% of the observed variation., while climate, price, and market vulnerabilities are reflected in the remainder. Qualitative data indicate that human, social, financial, physical, and natural capital improvements are strongly linked to recovery motivation, adaptive abilities, knowledge and skills, productive capital support, and sustained mentoring. Conclusion: The Livelihood Restoration Program acts as a catalyst for capacity building and asset strengthening, but its integration with more meaningful community engagement and cross-sectoral institutional reforms in geothermal and regional development policy is critical for durable livelihood resilience and social justice. Novelty/Originality of this article: This study contributes by integrating quantitative and qualitative evidence to explain how community engagement influences livelihood restoration and sustainable livelihood outcomes in geothermal development.